Employee Voice Behavior and its role in Organizational Ambidexterity: An analytical study of the opinions of a sample of employees and managers in mobile telecommunications companies in the Kurdistan Region-Iraq - عمر فتاح, ئاﭬﺎ; عباس خلوف, علي (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Purpose of the study: The current study seeks to indicate and determine the extent of the possibility of constructing Organizational Ambidexterity with its dimensions (exploring opportunities and exploiting opportunities) in light of the presence of the employee’s voice behavior represented by Promotive voice behavior and Prohibitive voice behavior in mobile telecommunications companies in Kurdistan Region of Iraq. Study problem: The study begins with the concern expressed by several intellectual and applied questions, and the main question of the study is "Does the employee’s voice behavior have a role in achieving Organizational Ambidexterity?" Design/methodology/approach: To achieve the objectives of the study and answer the questions of the study, the study adopted a descriptive-analytical approach, where the study variables and their dimensions were described by employees in a sample of the companies surveyed, and then a hypothetical model was formulated which reflects the nature of the correlation and influence relationships between the study variables, and its dimensions, which resulted in several main and sub-hypotheses, all of which were subjected to a set of analysis and statistical tests through a ready-made programs including AMOS-26, and SPSS-26. The telecommunications sector in Kurdistan Region was chosen as a field for the study, and the study sample represents 253 employees In 3 different companies listed in the Iraqi Communications Commission and the Ministry of Transport and Communications of Kurdistan Region-Iraq, It is worth noting that the researcher resorted to using many methods such as a questionnaire to collect data, and the researcher distributed the questionnaire electronically to employees via Google Forms, and after checking it was found that all of them are valid for analysis. Findings and Suggestions: Finally, the study reached a set of theoretical and field conclusions by presenting and analyzing the results of the hypotheses, the most prominent of which is that if the surveyed companies want to reach Organizational Ambidexterity, attention must be paid to the employee’s voice behavior, and the study also concluded that there is a significant and positive correlation and effect between the employee’s voice behavior and Organizational Ambidexterity. A set of proposals were presented with the mechanisms for their implementation, the most important of which is emphasis on the need for the researched companies to pay attention to the employee’s voice behavior and rely on it to continuously develop their services and the ability to survive and adapt in a rapidly changing work environment to build Organizational Ambidexterity.